The role of the solid state and physical properties of the carrier in adhesive mixtures for lung delivery. (3rd July 2018) - Della Bella, Andrea; Salomi, Enrico; Buttini, Francesca; Bettini, Ruggero
ABSTRACT: Introduction : Direct administration of drugs to the lung is commonly used for the treatment of local respiratory diseases, but it can also be employed to obtain a systemic effect. Besides the advantages offered in terms of higher therapeutic efficacy, this administration route raised specific drug delivery issues. In fact, to obtain a suitable bioavailability and therapeutic effect, the drug has to be efficiently deposited in the lower airways. Formulation is required to render the drug respirable. Area covered : The present paper deals with dry powders formulations, in particular it reviews the literature of the last two decades with respect to the role of the solid-state characteristics of the excipients used as carriers in adhesive mixture toward respirability of the active ingredient. Expert opinion : Many of the literature data on this topic are still not completely understood and sometimes they appear contradictory despite the intent to be complementary. More accurate and sensitive analytical methods for solid state characterization both for the drug and the carrier as well as a more systematic approach for the evaluation of the energetics of the carrier vs the drug surface is foreseen as a useful way to address some of the issues still opened in this field.